2022
DOI: 10.3389/fpsyg.2022.907050
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining eSports Industry and Regulatory Focus: Empirical Evidence From Chinese Universities

Abstract: This study examined the factors that affect the attitude and behavioral intentions toward electronic sports (eSports) among students of higher education institutions based on the technology acceptance model (TAM). The conditional impact of preventive regulatory focus was analyzed in various aspects developed on the regulatory focus theory. These aspects comprised of perceived usefulness, perceived ease of use, and perceived risk on the attitude toward eSports. Accordingly, data were collected from 293 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…As for the fans, they intentionally devote their spare time and finances to closely experience the competitions, meet their favorite players, and share their passions with other enthusiastic fans of similar interests. In the words of eSports tourists, live event attendance is considered to be a unique and unforgettable experience, deriving pleasure from satisfying vanity and snobbism [17,[44][45][46].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As for the fans, they intentionally devote their spare time and finances to closely experience the competitions, meet their favorite players, and share their passions with other enthusiastic fans of similar interests. In the words of eSports tourists, live event attendance is considered to be a unique and unforgettable experience, deriving pleasure from satisfying vanity and snobbism [17,[44][45][46].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…E-sports events and competitions are held either online or offline in arenas and stadiums (Exley and Bertram, 2021;Nikas and Poulaki, 2021). Some places are popular for holding e-sports tournaments including the USA, Asia, and Europe (Zhao et al, 2022;Jenny et al, 2018).…”
Section: Review 21 E-sportsmentioning
confidence: 99%
“…However, this study ignored a key predictor variable of behavioral intention – attitude ( Yan, 2014 ), as well as other relevant factors that matter in e-sports context, such as team identification and satisfaction with past experience. Similarly, a study conducted by Zhao et al (2022) in China’s Henan Province confirmed the significant positive impact of perceived usefulness and perceived ease of use on the attitude toward e-sports, while overlooking the explaining power of motivation on attitude and behavioral intention.…”
Section: Introductionmentioning
confidence: 99%